Production and Characterization of Briquettes from Agricultural Wastes for Sustainable Energy Solutions - Ahmed Umar; Abdulrahman Abdulmumin Gbenga; Muhammad-Najeeb Oluwafemi Yusuf; Abdulrasheed Faridah; Adeyemo Tijesunimi Emmanuel; Ajuwon Fadhilat Adekitan (ASEAN Journal for Science and Engineering in Materials, 2025)
The study evaluates the potential of rice husk (RH) and sawdust (SD) as energy sources by analyzing their physicochemical properties and combustion efficiencies. These common waste materials from Gwagwalada, Abuja, Nigeria, were processed into briquettes at varying ratios. Proximate analysis showed moisture content of 7.5–9.2% and ash content of 2.1–3.5%. Calorific values ranged from 18,509.84 kJ/kg (100% SD) to 22,658.77 kJ/kg (100% RH). The burning rate (BR) correlated with calorific value, with the 50:50 SD/RH mixture having the highest BR (0.003 g/min), indicating rapid combustion, while 100% SD had the lowest BR (0.0015 g/min), supporting slower combustion. All briquettes exhibited smokeless behavior, reducing greenhouse gas emissions and offering a clean energy alternative. This study highlights the potential of agricultural waste for energy security, environmental management, and rural economic development in Nigeria.